The Influence of Flash Sales and Paylater on Impulsive Buying Behavior Among Students of Universitas Muhammadiyah Purworejo on the Shopee E-Commerce Platform - Banati Istiqomah; Intan Puspitasari; Budiyanto (www.amertainstitute.com, 2025)
This study aims to determine and analyze the impact of flash sales and paylater options on the impulsive purchasing behavior of students at Muhammadiyah University Purworejo who use the Shopee e-commerce platform. The increasing tendency of students to make impulsive purchases underscores the relevance of this study, especially amid the surge in online shopping activities. Adopting a quantitative research design and survey methodology, the study targeted students of Muhammadiyah University of Purworejo who are Shopee users, with a total of 125 individuals serving as the sample. Data were gathered using questionnaires and analyzed through multiple linear regression with the help of SPSS (Statistical Product and Service Solutions). The results indicate that flash sale promotions independently have a positive impact on impulsive buying behavior. Similarly, the utilization of paylater services also contributes positively to students' tendencies to make unplanned purchases. These results suggest that digital marketing strategies, such as flash sales and paylater facilities, effectively encourage spontaneous purchasing decisions among students.